2021
DOI: 10.3390/ma14185381
|View full text |Cite
|
Sign up to set email alerts
|

Selected Strength Properties of Coal Bottom Ash (CBA) Concrete Containing Fly Ash under Different Curing and Drying Conditions

Abstract: This study aims to evaluate the effect of curing and drying conditions on the strength properties of concrete containing coal bottom ash (CBA) and fly ash as substitutes for fine aggregates and cement, respectively. The strength properties of the concrete including CBA and fly ash were evaluated under two different curing and drying conditions: saturated surface-dry (SSD) conditions and oven-dried conditions at curing ages of 28 and 91 days. The natural fine aggregates of the mixtures were replaced by CBA fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Despite being classified as fly ash type F and type C, the chemical composition of fly ash from various sources greatly varies, which means the classification alone could not represent the fly ash performance in a concrete mixture [12]. Moreover, several pieces of research also show that coal FABA in concrete increases the concrete drying time and reduces workability [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being classified as fly ash type F and type C, the chemical composition of fly ash from various sources greatly varies, which means the classification alone could not represent the fly ash performance in a concrete mixture [12]. Moreover, several pieces of research also show that coal FABA in concrete increases the concrete drying time and reduces workability [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Zaetang et al [ 8 ] reported that the insulating properties of porous concrete were increased by three to four times when lightweight coarse aggregates were used. Recently, coal bottom ash (CBA) has been progressively used in the construction industry due to its ability to replace cement or aggregate in concrete [ 9 , 10 ]. According to previous studies [ 9 , 11 , 12 , 13 ], the CBA particles contain micro- and macro-pores that make the density of CBA low.…”
Section: Introductionmentioning
confidence: 99%
“…Coal fly ash in concrete has several advantages, such as increasing the resistance to chloride penetration, sulphate attack, and alkali-silica reaction, lowering cracking due to drying and thermal shrinkage, improving the workability and reducing the water demand [22]. By contrast, most of the studies reported that coal fly ash provides early age compressive strength to the concrete [23,24], but at the later ages its contribution to compressive strength becomes larger. Furthermore, wet-curing periods result in lower compressive strength, and more porous and permeable concretes [25,26].…”
Section: Introductionmentioning
confidence: 99%